Linear lichen nitidus with onychodystrophy in a child - Vineet Relhan; Jaspriya Sandhu; Vijay Kumar Garg; Nita Khurana (Wolters Kluwer Medknow Publications, 2019)
Lichen nitidus is a common dermatosis described classically as shiny, skin-colored, nonfollicular, flat-topped papules. A number of variants have been described in literature including localized, generalized, actinic, vesicular, perforating, hemorrhagic, palmar/plantar, purpuric, and linear forms. Here, we report an unusual case of linear lichen nitidus in an 11-year-old boy mimicking lichen striatus along the left thumb with isolated nail involvement of the affected digit. Nail involvement in lichen nitidus is very rare; there are only seven cases of lichen nitidus associated nail changes reported in the literature. To the best of our knowledge, this is the first such case reported from India.